The relationship between (in)alienable possession and the (three potential) forms of possessed nouns in Hungarian - Farkas, Judit (Linguistica (Ljubljana), 2016)
The paper gives a thorough insight into the system of possible forms of (in)alienably possessed nouns in Hungarian. Its point of departure is the group of Nominative + -j- +A possessive forms the stem of which has an alternative (morphologically "shorter") possessive form; such longer possessive forms are claimed to express alienable possession (see den Dikken 2015). We point out that Hungarian deverbal nominals - and especially the groups of T-nouns - play an interesting role in this system via the thematic character of their possessors (given the obvious connection between alienable possession and external argumenthood, on the one hand, and inalienable possession and internal argumenthood, on the other).
Keywords: hongrois; Hungarian; madžarščina; morphologie; nom; oblikoslovje; possession inaliénable; samostalnik; svojilnost